Application of image processing to assess emulsion stability and emulsification properties of Arabic gum. (1st August 2015) - Hosseini, Abdullah; Jafari, Seid Mahdi; Mirzaei, Habibollah; Asghari, Ali; Akhavan, Sahar
Highlights: Image processing was used to determine emulsion stability. For each response, a second-order polynomial model was developed. The formulated emulsions under optimized conditions had 99.20% stability. Abstract: This paper focuses on the development of an effective methodology to determine the optimum levels of independent variables leading to maximize stability of O/W emulsions containing Arabic gum, as a natural emulsifier and stabilizer. Response surface methodology (RSM) was employed to determine the effect of Arabic gum content (2%, 5%, and 8% (w/w)), homogenization time (5, 12.5, and 20 min) and storage temperature (4, 22, and 40 °C). Image processing was used to determine emulsion stability based on responses including creaming index, centrifugal stability, viscosity, color parameters, and D 32 and D 43 indices. For each response, a second-order polynomial model with high coefficient of determination ( R 2 ) values ranging from 0.95 to 0.989 was developed using multiple linear regression analysis. The optimization results showed that the overall optimum region with the highest stability was found to be at the combined levels of 5.81% (w/w) Arabic gum content, 5 min homogenization time, and 22 °C for storage temperature.